Comparing systemic therapy and cognitive behavioral therapy for social anxiety disorders: study protocol for a randomized controlled pilot trial - Hunger-Schoppe, Christina; Hilzinger, Rebecca; Koch, Theresa; Mander, Johannes; Sander, Anja; Bents, Hinrich; Schweitzer, Jochen (Trials, 2016)
Background: Social anxiety disorders are among the most prevalent anxiety disorders in the general population. The efficacy of cognitive behavioral therapy (CBT) for social anxiety disorders is well demonstrated. However, only three studies point to the efficacy of systemic therapy (ST) in anxiety disorders, and only two of them especially focus on social anxiety disorders. These ST studies either do not use a good comparator but minimal supportive therapy, they do not use a multi-person ST but a combined therapy, or they do not especially focus on social anxiety disorders but mood and anxiety disorders in general. Though ST was approved as evidence based in Germany for a variety of disorders in 2008, evidence did not include anxiety disorders. This is the first pilot study that will investigate multi-person ST, integrating a broad range of systemic methods, specifically for social anxiety disorders and that will compare ST to the "gold standard" CBT. Design: This article describes the rationale and protocol of a prospective, open, interventive, balanced, bi-centric, pilot randomized controlled trial (RCT). A total of 32 patients with a primary SCID diagnosis of social anxiety disorder will be randomized to either CBT or ST. Both treatments will be manualized. The primary outcome will include social anxiety symptoms at the end of therapy. Therapy will be restricted to no more than 26 hours (primary endpoint). Secondary outcomes will include psychological, social systems and interpersonal functioning, symptom adjustment, and caregiver burden, in addition to change measures, therapist variables and treatment adherence. At the secondary endpoints, 9 and 12 months after the beginning of therapy, we will again assess all outcomes. Discussion: The study is expected to pilot test a RCT which will be the first to directly compare CBT and multi-person ST, integrating a broad range of systemic methods, for social anxiety disorders, and it will provide empirical evidence for the calculation of the number of patients needed for a confirmatory RCT.